Age at menarche in Russian women is associated with the ESR2 candidate gene - E. A. Reshetnikov; I. V. Ponomarenko; M. I. Churnosov (IRBIS LLC, 2021)
Aim: to study a relation between a single-nucleotide polymorphism in the estrogen receptor beta (ESR2) gene and age of menarche in women of the Central Black Earth region of Russia.Materials and Мethods. There were enrolled 696 women to the retrospective study. All subjects were interrogated data regarding the age of menarche. Three polymorphic loci rs4986938, rs1256031, and rs10144225 of the ESR2 gene were genotyped by using the TaqMan probe polymerase chain reaction. The functional epigenetic effects of the rs4986938 ESR2 menarche-associated polymorphism were studied by using the online HaploReg software.Results. There were found out associations of ESR2 rs4986938 polymorphism with the age of menarche in Russian women of the Central Black Earth region of the Russian Federation. Women with the rs4986938 ESR2 polymorphism allele A in the genotype (genotypes A/A and G/A) had menarche at the age of 12.71 ± 1.03 years, which is 0.20 years later than in women lacking it in the genotype (genotype G/G), who had menarche at age of 12.51 ± 1.05 years (pperm = 0,01). The rs4986938 ESR2 polymorphism is characterized by pronounced epigenetic effects: it affects affinity for five transcription factors - CTCF, Nr2f2, Pax-6, Pax-8, and RAR, being associated with enhancer and promoter sites in various menarche-significant body tissues and organs, and associated with the expression of the ESR2 geneepigenetic effects: it affects affinity for five transcription factors - CTCF, Nr2f2, Pax-6, Pax-8, and RAR, being associated with enhancer and promoter sites in various menarche-significant body tissues and organs, and associated with the expression of the ESR2 gene.Conclusion. The rs4986938 polymorphic locus of the ESR2 gene is associated with age of menarche in women in the European part of Russia.